FRAMEWORK OF PROFESSIONAL COMPETENCIES OF EDUCATORS: A CASE RESEARCH OF TEACHERS IN WESTERN KAZAKHSTAN - Сейтенова, Салима; MUSAGALIEVA, G.; SHANDOZTEGI А.; BESSMERTNOV, P.; RAMAZANOVA, A. (Pedagogy and Psychology, 2025)
This research focuses on analyzing the professional competencies of educators in Western Kazakhstan within the context of contemporary educational challenges. Using a qualitative approach and phenomenological design, semi-structured interviews were conducted with 13 teachers to examine their perception and implementation of professional competencies. The research revealed a common understanding of competencies as a complex of knowledge, skills, and abilities, but also uncovered significant discrepancies between theoretical understanding and practical implementation, especially in the areas of digital and research competencies. The results showed a high appreciation for the importance of social-emotional competencies, but insufficient attention to the development of digital skills and research practices. The research identified the need for a more structured approach to developing professional competencies and systemic changes in teacher training. It emphasizes the importance of developing a comprehensive framework of professional competencies that takes into account all aspects of modern pedagogical activity. Recommendations include strengthening training in digital technologies, integrating research competencies into professional development programs, and creating a support system for continuous professional development of teachers.